Factors affecting the emotional intelligence of adolescents during the COVID-19 pandemic: a descriptive study in South Korea - Kyungmi Lee; Hyosung Cha (Child Health Nursing Research)
Purpose This descriptive study aimed to identify the factors affecting adolescents’ emotional intelligence during the COVID-19 (coronavirus disease 2019) pandemic. Methods We utilized the 4th-year data from the 2018 Korean Children and Youth Panel Survey, which comprise 1,852 adolescents living with both parents. The determinants of adolescents’ emotional intelligence were analyzed through stepwise multiple regression, considering parental, family, and school factors. Results Parental factors, such as parents’ grit and emotional intelligence, were found to enhance adolescents’ emotional intelligence. Family factors, including parents’ positive parenting attitude and the average time spent with parents, also significantly enhance adolescents’ emotional intelligence. School factors, such as the number of remote class days during the previous semester, influenced adolescents’ emotional intelligence. Conclusion Parental and family factors enhanced emotional intelligence, whereas school factors, particularly remote learning, negatively impacted it. The model explained 67.5% of variance, with parents' emotional intelligence being the strongest predictor. Interventions should prioritize enhancing parental emotional competence and maintaining meaningful parent-child interactions, especially during educational disruptions.